Anti-cancer effect and potential microRNAs targets of ginsenosides against breast cancer - Fan, Meiling; Shan, Mengyao; Lan, Xintian; Fang, Xiaoxue; Song, Dimeng; Luo, Haoming; Wu, Donglu (Frontiers in Pharmacology, 2022)
Breast cancer (BC) is one of the most common malignant tumor, the incidence of which has increased worldwide in recent years. Ginsenosides are the main active components of Panax ginseng C. A. Mey., in vitro and in vivo studies have confirmed that ginsenosides have significant anti-cancer activity, including BC. It is reported that ginsenosides can induce BC cells apoptosis, inhibit BC cells proliferation, migration, invasion, as well as autophagy and angiogenesis, thereby suppress the procession of BC. In this review, the therapeutic effects and the molecular mechanisms of ginsenosides on BC will be summarized. And the combination strategy of ginsenosides with other drugs on BC will also be discussed. In addition, epigenetic changes, especially microRNAs (miRNAs) targeted by ginsenosides in the treatment of BC are clarified.